2006
DOI: 10.1111/j.1467-7652.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Suspension‐cultured BY‐2 tobacco cells produce and mature immunologically active house dust mite allergens

Abstract: SummaryThe replacement of crude allergen extracts by selected allergens currently represents a major goal for the improvement of allergy diagnosis and immunotherapy. Indeed, the development of molecularly defined vaccines would facilitate both standardization and enhance batch-to-batch reproducibility as well as treatment specificity. In this study, we have investigated the potential of tobacco plant cells to produce biologically active forms of the two major allergens from the house dust mite. A detailed char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 53 publications
3
22
0
1
Order By: Relevance
“…Der p 2 has been produced successfully in various cell expression systems, including Escherichia coli, the yeast Saccharomyces cerevisiae and tobacco cells [11,12,13]. Der p 1 is a more complex protein expressed as a preproenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Der p 2 has been produced successfully in various cell expression systems, including Escherichia coli, the yeast Saccharomyces cerevisiae and tobacco cells [11,12,13]. Der p 1 is a more complex protein expressed as a preproenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported a successful expression of recombinant Der p 2 in E. coli , alone or as a fusion protein with glutathione-S-transferase or Der p 1 [29,37,49,50,51] as well as in eukaryotic hosts such as Saccharomyces cerevisiae [30,52] and tobacco cells [32]. Some of these molecules were found to resemble the natural counterpart in terms of antigenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although Der p 2 has been previously produced in a recombinant form in a variety of expression systems [29,30,31,32], as of today, none of these studies has documented a bona fide natural conformation of the molecule to a level fulfilling the requirements for human administration. As Der p 2 exists as a variety of isoforms/variants [33,34,35], we first selected a prominent isoform following a mass spectrometry (MS) analysis of mite extracts.…”
Section: Introductionmentioning
confidence: 99%
“…(Gomord et al 1997 ;Ma et al 2003 ;Chou and Shen 2010 ), directing the protein to the secretor pathway to collect it from the culture medium (e.g. : in in vitro cultures) (Hellwig et al 2004 ;Komarnytsky et al 2006 ;Lienard et al 2007 ;Benchabane et al 2008 ), co-expressing the protein with protease inhibitors (Faye et al 2005 ;Michaud et al 2005 ;Komarnytsky et al 2006 ), or expressing the recombinant protein as a fusion protein with a stable and highly expressed peptide (Nygren et al 1994 ;Stahl et al 1997 ).…”
Section: Plant Cell Levelmentioning
confidence: 99%